Singular Reduction of Generalized Complex Manifolds - Goldberg, T.E. (Symmetry, Integrability and Geometry: Methods and Applications, 2010)
In this paper, we develop results in the direction of an analogue of Sjamaar and Lerman's singular reduction of Hamiltonian symplectic manifolds in the context of reduction of Hamiltonian generalized complex manifolds (in the sense of Lin and Tolman). Specifically, we prove that if a compact Lie group acts on a generalized complex manifold in a Hamiltonian fashion, then the partition of the global quotient by orbit types induces a partition of the Lin-Tolman quotient into generalized complex manifolds. This result holds also for the reduction of Hamiltonian generalized Kähler manifolds.